A medium‐term, stochastic forecast model to support sustainable, mixed fisheries management in the Mediterranean Seaa. Issue 4 (1st October 2013) - Rätz, H.‐J.; Charef, A.; Abella, A. J.; Colloca, F.; Ligas, A.; Mannini, A.; Lloret, J.
<x xml:space="preserve">Abstract</x> A medium‐term (10 year) stochastic forecast model is developed and presented for mixed fisheries that can provide estimations of age‐specific parameters for a maximum of 10 stocks and 10 fisheries. Designed to support fishery managers dealing with complex, multi‐annual management plans, the model can be used to quantitatively test the consequences of various stock‐specific and fishery‐specific decisions, using non‐equilibrium stock dynamics. Such decisions include fishing restrictions and other strategies aimed at achieving sustainable mixed fisheries consistent with the concept of maximum sustainable yield (MSY). In order to test the model, recently gathered data on seven stocks and four fisheries operating in the Ligurian and North Tyrrhenian Seas are used to generate quantitative, 10 year predictions of biomass and catch trends under four different management scenarios. The results show that using the fishing mortality at MSY as the biological reference point for the management of all stocks would be a strong incentive to reduce the technical interactions among concurrent fishing strategies. This would optimize the stock‐specific exploitation and be consistent with sustainability criteria.